The English Government Hits Limits: Knowledge Politics and Covid-19 - May, Tim (Frontiers in Sociology, 2021)
Tragic its consequences, the Covid-19 pandemic has ripped through societies with, at the time of writing, global death rates exceeding two and a half million people. In the process, there has been variability in terms of how effectively governments have dealt with the pandemic. Differences between political responses, forms of governance and the relationships between science and politics are apparent. This article investigates these relations in the United Kingdom with a particular focus upon the interpretations that informed the response of the English Government and their interactions with the scientific community. For this purpose, it provides an exploration of the political and socio-economic conditions prevailing in the U.K. prior to the pandemic. It then examines the interactions between science and politics as the pandemic unfolded during 2020. Then, building on these discussions it views the tensions that arose through a clash between two characteristics within democratic societies: the redemptive and pragmatic. What becomes apparent is the tendency for a form of the redemptive to be favoured over the pragmatic which results in an exposure of limits to usual and narrow political ways of governing.